Preventing Cognitive Decline in Late-Life Depression: A Longitudinal Study on the Efficacy of Omega-3 Fatty Acid Supplementation in Older Adults in Palembang, Indonesia - Sony Sanjaya; Febria Suryani; Pham Uyen; Maria Rodriguez; Muhammad Yoshandi (Scientia Psychiatrica, 2025)
Introduction: Late-life depression (LLD) is a prevalent condition in older adults and a significant risk factor for cognitive decline and dementia. In Indonesia, with its aging population and specific dietary patterns, understanding interventions for LLD-associated cognitive impairment is crucial. Omega-3 polyunsaturated fatty acids (PUFAs) offer potential neuroprotective benefits. This study aimed to assess the efficacy of long-term omega-3 PUFA supplementation in mitigating cognitive decline among older adults with LLD in Palembang, Indonesia. Methods: This 24-month, randomized, double-blind, placebo-controlled trial was conducted in Palembang. Three hundred sixty older adults (aged ≥60 years) with a current DSM-5 diagnosis of Major Depressive Disorder (MDD) and subjective cognitive complaints were randomized (1:1) to receive either daily oral supplementation of 2.2 grams of omega-3 PUFAs (containing 1320 mg eicosapentaenoic acid [EPA] and 880 mg docosahexaenoic acid [DHA]) or a matched placebo (corn oil). The primary outcome was the change in the Indonesian version of the Alzheimer's Disease Assessment Scale-Cognitive Subscale (ADAS-Cog-INA) score over 24 months. Secondary outcomes included changes in the Montreal Cognitive Assessment-Indonesian version (MoCA-INA), Geriatric Depression Scale (GDS-30), Instrumental Activities of Daily Living (IADL), serum Brain-Derived Neurotrophic Factor (BDNF), and high-sensitivity C-Reactive Protein (hs-CRP). Results: Over 24 months, the omega-3 group exhibited significantly less decline on the ADAS-Cog-INA compared to the placebo group (mean difference: -2.1 points; 95% CI: -3.8 to -0.4; p=0.018). Statistically significant benefits for the omega-3 group were also observed in MoCA-INA scores (mean difference: 1.5 points; p=0.025) and GDS-30 scores (mean difference: -2.5 points; p=0.011). BDNF levels increased significantly in the omega-3 group relative to placebo (p=0.008), while hs-CRP levels showed a non-significant trend towards reduction (p=0.072). Conclusion: Long-term supplementation with 2.2 g/day of EPA-rich omega-3 PUFAs resulted in a modest but statistically significant attenuation of cognitive decline and improvement in depressive symptoms in older adults with LLD in Palembang. These findings suggest that omega-3 PUFAs could be a valuable adjunctive therapeutic strategy in this specific Southeast Asian population.